DEVELOPMENT OF TEACHING MATERIALS FOR WRITING SCIENTIFIC WORKS BASED ON DIGITAL LEARNING FOR STUDENTS OF THE INDONESIAN LANGUAGE EDUCATION STUDY PROGRAM, FACULTY OF TEACHER TRAINING AND EDUCATION, UNIVERSITY OF MUHAMMADIYAH BONE - Andi Srimularahmah; Mantasiah R (Adisam Publisher, 2025)
This research belongs to the type of R&D (Research and Development) development research that aims to produce prototypes, to assess the feasibility, practicality, and effectiveness of teaching materials for writing scientific papers based on digital learning for students of the Indonesian Language Education Study Program, Faculty of Teacher Training and Education, University of Muhammadiyah Bone. In this study, the Dick and Carey development model was adapted into five stages, namely: (1) preliminary study stage; (2) design stage; (3) development stage; (4) evaluation and revision stage; and (5) dissemination stage. The test subjects were teaching material experts, learning media experts, and students of the Indonesian Language Education Study Program. To get data on the feasibility of teaching materials, a feasibility sheet of materials and learning media is needed. Furthermore, to get data on the practicality of teaching materials, student response questionnaire data is needed. Effectiveness data is obtained from student pretest and posttest learning outcomes, before and after using digital learning-based scientific writing materials. The data analysis technique used is quantitative data analysis for the feasibility, practicality, and effectiveness of teaching materials. Then descriptive statistical data analysis and polygon analysis to analyze student pretest and posttest learning outcomes. The results showed that each topic on learning resources and learning activities in the first stage M = 3.5 and the second stage M = 4 were in the very feasible category (3.5≤ M ≤ 4). The total average value of the percentage of student responses in the second stage is M = 4 in the very feasible category (3.5 ≤ M ≤ 4). The total percentage value of student responses who agreed in learning to write scientific papers based on digital learning was 98.5%, in the very practical category, namely (86%-100%). The average value of posttest students in learning obtained is 83.7 in the range (≥75 -≤100). Based on the results of the data analysis, it can be concluded that the development of teaching aids for writing scientific papers based on digital learning is feasible, practical, and effective in use by students of the Indonesian Language Education Study Program, Faculty of Teacher Training and Education, Muhammadiyah Bone University.